Akibat Hukum Terhadap Notaris Yang Rangkap Jabatan Sebagai Advokat Di Kota Bandar Lampung - Andriansyah Kartadinata; Irwan Jaya Diwirya; Satrya Surya Pratama (Universitas Sang Bumi Ruwa Jurai, 2023)
Notaries in making authentic deeds are guaranteed by law, so notaries mean that they have a very noble position, have high dignity because the position of notary is given by the government on behalf of the state to meet the needs of society in the field of civil law. Efforts to maintain the good name of the notary's position, in carrying out their duties, the notary has certain restrictions that must be obeyed, the notary may also not perform other work that is contrary to religious norms, decency or propriety that may affect the honor and dignity of a notary based on statutory provisions and professional code of ethics. The legal issues discussed in this paper are the legal consequences of a notary having concurrent positions, as well as the position of the deed issued by the notary.The method used in this study uses legal research, which is an alternative approach that examines doctrinal studies of law with regard to the legal issues studied, namely the legal consequences of the notary's position and the deeds he made and are associated with the theory of legal certainty as the basis for the regulations that have been made and promulgated, runs clearly, logically, and does not cause multiple interpretations.The results of the discussion explain that the legal consequences of a notary who holds concurrent positions as an advocate, the notary's profession does not solely apply as stipulated in the legislation and professional code of ethics, and the legal consequences of a deed issued by a notary if the notary holds concurrent positions is equivalent to an underhanded or void agreement by law.The conclusion drawn from this research is that notaries are not allowed to hold concurrent positions in order to protect the notary professional organization so that conflicts of interest do not occur, while the legal consequences of a deed made when a notary is subject to sanctions due to concurrent positions loses the form of an authentic deed.